IPTF16abc and the population of Type Ia supernovae: comparing the photospheric, transitional, and nebular phases. Issue 2 (20th July 2018) - Dhawan, S; Bulla, M; Goobar, A; Lunnan, R; Johansson, J; Fransson, C; Kulkarni, S R; Papadogiannakis, S; Miller, A A
ABSTRACT: Key information about the progenitor system and the explosion mechanism of Type Ia supernovae (SNe Ia) can be obtained from early observations, within a few days from explosion. iPTF16abc was discovered as a young SN Ia with excellent early time data. Here, we present photometry and spectroscopy of the SN in the nebular phase. A comparison of the early time data with a sample of SNe Ia shows distinct features, differing from normal SNe Ia at early phases but similar to normal SNe Ia at a few weeks after maximum light (i.e. the transitional phase) and well into the nebular phase. The transparency time-scales ( t 0 ) for this sample of SNe Ia range between ∼25 and 41 d indicating a diversity in the ejecta masses. t 0 also weakly correlates with the peak bolometric luminosity, consistent with the interpretation that SNe with higher ejecta masses would produce more $\rm ^{56}Ni$  . Comparing the t 0 and the maximum luminosity, L max  distribution of a sample of SNe Ia to predictions from a wide range of explosion models we find an indication that the sub-Chandrasekhar mass models span the range of observed values. However, the bright end of the distribution can be better explained by Chandrasekhar mass delayed detonation models, hinting at multiple progenitor channels to explain the observed bolometric properties of SNe Ia. iPTF16abc appears to be consistent with the predictions from the M ch  models.